The Impact of ODI on Transformational Leadership, Job Satisfaction, Organizational Citizenship Behavior, Employee Motivation, and Employee Engagement: A Case Study of BG Coffee Company in Pu’er City, Yunnan, China - Li, Mengke; Tantasanee, Somchai; Clancy, Ann (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study aims to explore the impact of organizational development intervention (ODI) on transformational leadership, organizational citizenship behavior (OCB), job satisfaction, employee motivation, and engagement at BG Coffee Company located in Pu’er City, China. The action research is divided into three distinct phases: pre-intervention, during intervention, and post-intervention. The research design adopts a mixed-method approach, combining qualitative analysis with a quantitative survey of 30 employees. Data was analyzed using descriptive statistics and paired sample t-tests. The intervention strategy included the introduction of The World Café, a participatory dialogue method that aligns with the principles of self-determination theory. The results show that there were statistically significant differences (p < 0.05) in all measured indicators, including transformational leadership, OCB, job satisfaction, motivation, and engagement before and after the intervention. Qualitative research results further confirm that ODI helps to align cultural norms with intrinsic motivation, especially through participatory methods that meet psychological needs such as autonomy, competence, and relatedness. This study highlights the practical value of ODI in promoting adaptive organizational culture in small and medium-sized enterprises (SMEs) and provides scalable strategies applicable to multinational companies. Although the current study mainly focuses on leadership and front-line employees, future research can explore the organizational dynamics between coffee growers and managers. These empirical findings contribute to understanding how structured interventions can systematically improve workplace outcomes in China’s booming specialty coffee industry while emphasizing the key role of employee-centered development in promoting sustainable business practices.